Antidiabetic efficacy of methanolic extract of the leaves of Tetracera Indica Merr. (Dilleniaceace) in alloxan induced diabetic rats - S. Dogarai, Bashar Bello; Ahmed, Qamar Uddin; Umar, Abdulrashid (Penerbit USM, 2010)
Introduction: Tetracera indica Merr., (mempelas paya) is used in Malaysia and other parts of South-Asia as a folk medicine to treat fever, flu, skin rashes, itching, piles, mouth ulcer, diabetes, and insects bites. Objective: The study has been carried out to screen the antidiabetic efficacy of methanolic extract (MeOH) of the leaves of T. indica in vivo in alloxan induced diabetic and normal rats.